2022
DOI: 10.1093/jme/tjab225
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Situation of Human African Trypanosomiasis in the Republic of Congo From the 1950s to 2020

Abstract: Human African trypanosomiasis (HAT), despite considerable progress in the control, is still occurring in many countries in both west and central African regions. The HAT situation in the Republic of Congo has always been overshadowed by its neighbor the Democratic Republic of Congo where over 60% of all HAT cases occur. In the Republic of Congo, HAT cases have been significantly reduced to about 20 reported cases yearly and the disease is still prevalent in few foci across the country. Although continuous asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Furthermore, we found that the participants aged more than 15 years were more infected by HAT compared to the other age groups. HAT cases was significantly predominant in Mindouli and Mpouya districts, with a high risk of the infection, confirming what has been reported previously [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, we found that the participants aged more than 15 years were more infected by HAT compared to the other age groups. HAT cases was significantly predominant in Mindouli and Mpouya districts, with a high risk of the infection, confirming what has been reported previously [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…Many studies reported that the Glossina species identified as the main vector of the T. b. gambiense infection in Congo feed on both human and animal and always display infectivity [ 12 ]. All this suggests that more efforts are still needed for the eradication of the disease in these districts, both in human and animal population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation